2016
DOI: 10.1089/mdr.2015.0124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotics and Antibiofilm Agents in the Ultrastructure and Development of Biofilms Developed by Nonpigmented Rapidly Growing Mycobacteria

Abstract: We analyze the effect of amikacin, ciprofloxacin, and clarithromycin, alone and associated with N-acetylcysteine (NAC) and Tween 80, at different times and concentrations in nonpigmented rapidly growing mycobacteria (NPRGM) biofilms. For this purpose, confocal laser scanning microscopy and image analysis were used to study the development and behavior of intrinsic autofluorescence, covered area, thickness, and cell viability in NPRGM biofilms after adding antibiotics alone and associated with antibiofilm agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…In this study, we manifested the antimicrobial and antibiofilm effects of NAC and ciprofloxacin, each alone and in combination in bone cement against P. aeruginosa . Although there are some studies indicating antimicrobial and antibiofilm effects of that agents (Dinicola et al ., ; Munoz‐Egea et al ., ), to our knowledge, there are no studies demonstrating those effects on P. aeruginosa biofilms in bone cement. Furthermore, quantitative evaluation of bone cement samples using SEM also is the first approach in the literature.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, we manifested the antimicrobial and antibiofilm effects of NAC and ciprofloxacin, each alone and in combination in bone cement against P. aeruginosa . Although there are some studies indicating antimicrobial and antibiofilm effects of that agents (Dinicola et al ., ; Munoz‐Egea et al ., ), to our knowledge, there are no studies demonstrating those effects on P. aeruginosa biofilms in bone cement. Furthermore, quantitative evaluation of bone cement samples using SEM also is the first approach in the literature.…”
Section: Discussionmentioning
confidence: 86%
“…Muñoz-Egea et al found differences between the MIC and minimum biofilm eradication concentration (MBEC) in 4 species of RGM, ranging between <100-fold in the case of Mycobacterium mucogenicum exposed to ciprofloxacin, and >100,000-fold in the case of M. abscessus and Mycobacterium peregrinum exposed to clarithromycin (Muñoz-Egea et al, 2015 ); ciprofloxacin was the most active antibiotic against these biofilms, compared with clarithromycin or amikacin. Further studies have shown the effect of antibiotic therapy in different stages of biofilm development (Muñoz-Egea et al, 2015 , 2016b ). In these studies, treatment of the biofilm was more effective when antibiotics are added in the early stage of biofilm development, probably because the phenotype of the cells is not fully adapted to biofilm growth.…”
Section: Mycobacterial Biofilms In Medicine: Therapeutic Implicationsmentioning
confidence: 99%
“…Tween 80 alters the structural integrity of the membrane, lipids, and proteins (Teixeira et al, 2007 ), while NAC acts on the polysaccharide matrix of the biofilm, breaking disulfide bridges that link the polysaccharide fibers (Olofsson et al, 2003 ). Due to the high lipid content of the mycobacterial cell wall and the significant presence of lipids in the extracellular matrix, Tween 80 is more active against mycobacterial biofilm than NAC (Muñoz-Egea et al, 2016b ). An increase in antibacterial activity was observed when NAC and Tween 80 were combined with ciprofloxacin, clarithromycin, and amikacin.…”
Section: Mycobacterial Biofilms In Medicine: Therapeutic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Ortíz-Pérez et al (2011) on biofilm-producing RGM treated with antibiotics showed that biofilms are resistant to AMK, CLR and ciprofloxacin (CIP) [363]. Among these three antibiotics, CIP is the most active drug affecting the thickness of the biofilms and its combination with anti-biofilm agents such as N-acetylcysteine (NAC) and Tween 80 have resulted in higher bacterial death [364].…”
Section: (B) Treatmentmentioning
confidence: 99%